Hyperbaric oxygen facilitates teniposide-induced cGAS-STING activation to enhance the antitumor efficacy of PD-1 antibody in HCC. Issue 8 (24th August 2022) - Li, Kun; Gong, Yihang; Qiu, Dongbo; Tang, Hui; Zhang, Jian; Yuan, Zenan; Huang, Yingqi; Qin, Yunfei; Ye, Linsen; Yang, Yang
Abstract : Background: Emerging evidence indicates that the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) axis plays a pivotal role in intrinsic antitumor immunity. Previous studies demonstrate that the conventional chemotherapy agent, teniposide, effectively promotes the therapeutic efficacy of programmed cell death protein-1 antibody (PD-1 Ab) through robust cGAS-STING activation. Unfortunately, the cGAS expression of tumor cells is reported to be severely suppressed by the hypoxic status in solid tumor. Clinically, enhancing chemotherapy-induced, DNA-activated tumor STING signaling by alleviating tumor hypoxia might be one possible direction for improving the currently poor response rates of patients with hepatocellular carcinoma (HCC) to PD-1 Ab. Methods: Teniposide was first screened out from several chemotherapy drugs according to their potency in inducing cGAS-STING signaling in human HCC cells. Teniposide-treated HCC cells were then cultured under hypoxia, normoxia or reoxygenation condition to detect change in cGAS-STING signaling. Next, oxaliplatin/teniposide chemotherapy alone or combined with hyperbaric oxygen (HBO) therapy was administered on liver orthotopic mouse tumor models, after which the tumor microenvironment (TME) was surveyed. Lastly, teniposide alone or combined with HBO was performed on multiple mouse tumor models and the subsequent anti-PD-1 therapeutic responses were observed. Results: Compared with the first-line oxaliplatin chemotherapy, teniposide chemotherapy induced stronger cGAS-STING signaling in human HCC cells. Teniposide-induced cGAS-STING activation was significantly inhibited by hypoxia inducible factor 1α in an oxygen-deficient environment in vitro and the inhibition was rapidly removed via effective reoxygenation. HBO remarkably enhanced the cGAS-STING-dependent tumor type Ⅰ interferon and nuclear factor kappa-B signaling induced by teniposide in vivo, both of which contributed to the activation of dendritic cells and subsequent cytotoxic T cells. Combined HBO with teniposide chemotherapy improved the therapeutic effect of PD-1 Ab in multiple tumor models. Conclusions: By combination of two therapies approved by the Food and Drug Administration, we safely stimulated an immunogenic, T cell-inflamed HCC TME, leading to further sensitization of tumors to anti-PD-1 immunotherapy. These findings might enrich therapeutic strategies for advanced HCC andwe can attempt to improve the response rates of patients with HCC to PD-1 Ab by enhancing DNA-activated STING signaling through effective tumor reoxygenation.